Analisis Strategi Pemanfaatan Akun Instagram @telkomakses_batam Dalam Menciptakan Citra Perusahaan - prastyo, gani; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2024)
This research analyzes the strategic role of Instagram account @TelkomAkses_Batam in shaping the positiveimage of PT Telkom Akses in Batam. With a qualitative descriptive method, the focus is on the communicationand strategy aspects of the company in the operational office of PT Telkom Akses Batam. Data collectioninvolves interviews, observation, documentation, and literature study. The company implemented acommunication policy with emphasis on verbal communication and Telegram group chat media. A planned CSRstrategy shows the company's positive commitment to the community. The management of the@telkomakses_batam Instagram account involves several divisions, demonstrating a collaborative approach.Diversification of Instagram content is necessary to maintain audience interest. Continuous CSR programs andincreased positive communication can increase viewer understanding. Employee engagement can be improvedthrough inter-divisional collaboration and creating a proactive work environment. This research provides an indepth insight into the effectiveness of corporate communication strategies through Instagram in shaping apositive image in the digital era